2016
DOI: 10.1021/acs.organomet.6b00427
|View full text |Cite
|
Sign up to set email alerts
|

Borata-Alkene Derived Syntheses of (F5C6)2B-Substituted Bis(indenyl) Group 4 Metal Complexes

Abstract: An indene based borata-alkene was used as a reagent for the synthesis of B­(C6F5)2-functionalized group 4 bent-metallocene complexes. The respective borata-alkene was prepared by HB­(C6F5)2 hydroboration of dimethylbenzofulvene followed by deprotonation with lithium tetramethylpiperidide. Treatment of CpTiCl3 or CpZrCl3 with the borata-alkene gave the respective [(C6F5)2B-indenyl]­CpMCl2 bent-metallocene complexes. Both were characterized by X-ray diffraction. The boryl-functionalized metallocenes gave active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…In this case, η 5 -indenyl coordination to zirconium was favoured to give the boryl-functionalized bent metallocene complex 23 . 15 In the presence of AlEt 3 complex 23 gave an active ethylene and propene polymerization catalyst.…”
Section: The Borataalkenesmentioning
confidence: 99%
“…In this case, η 5 -indenyl coordination to zirconium was favoured to give the boryl-functionalized bent metallocene complex 23 . 15 In the presence of AlEt 3 complex 23 gave an active ethylene and propene polymerization catalyst.…”
Section: The Borataalkenesmentioning
confidence: 99%
“…[51] Erker and co‐workers also observed that indene based borata‐alkene species 4 could be used as ligand to react with CpZrCl 3 towards the formation of bent‐metallocene complex [(C 6 F 5 ) 2 B‐indenyl]CpZrCl 2 ( 36 ) (Figure 5). [52a] Characterization by X‐ray diffraction and NMR concluded that a short B−C bond length (1.505(4) Å) is present in the complex indicating some slight residual borata fulvene character in the structure of the bent‐metallocene complex 36 . The same authors have described the synthesis and complete characterization by X‐ray diffraction of a rhodium complex 37 containing a P/C=B chelate ligand, in a distorted square‐planar coordination geometry at rhodium (Figure 5).…”
Section: Characterization Of Borata‐alkene Speciesmentioning
confidence: 99%